Analisis Gaya Bahasa Dalam Acara Talkshow Shihab-Shihab - Dedi Dedi; Dewi Herlina Sugiarti; Sinta Rosalina (Peneliti.net, 2022)
The thing that is most needed in a lecture is the use of language style. In lectures, language style has an implementation in conveying the contents of religious teachings. The style of language in lectures can be used as a reflection of the character of the preacher and is a characteristic of the speaker's activity. The purpose of this study is to describe the style of language in the Shihab-Shihab talk show. This study uses a qualitative approach and analytic descriptive method. Data collection techniques used listening techniques, note-taking techniques, and proficient free engagement techniques. Data collection techniques include data reduction, data presentation, and drawing conclusions or verification. The results of the analysis show that there are 15 Euphemisms, 4 Antonomasia, 4 Erotesis, 5 Parallelisms, 2 Anaphora, 1 Parable, 4 Personification, 2 Antithesis, 1 Alliteration, and 1 Anadiplosis. Based on these findings, it shows that the speaker has a variety of language styles.